Structuring Hydrogel Surfaces for Tribology - Gombert, Yvonne; Simič, Rok; Roncoroni, Fabrice; Dübner, Matthias; Geue, Thomas; Spencer, Nicholas D. (Advanced materials interfaces, 2019)
Hydrogels are often used as model systems for articular cartilage due to similarities in their tribological properties. However, neither the structures nor the friction mechanisms of either system are fully understood. A key aspect of hydrogel lubrication is the nature of the polymeric structure at the surface, and the lubricating water film. A combination of neutron reflectometry and infrared spectroscopy is used to probe polymer volume fraction from the interface into the bulk hydrogel and its dependence on the molding material. The depth dependence of the polymer‐network density influences the compressibility of the hydrogel surfaces, as demonstrated by both atomic force microscopy (AFM)‐ and micro indentation. By changing molding materials, substantial differences in the gradient of polymer‐network density are observed with depth. The lower the volume fraction of polymer at the hydrogel surface, the more water it can maintain at its interface as a substantial water film that is stable even under static conditions. Such films render the hydrogel highly lubricious, with a speed‐independent friction coefficient of μ = 0.01, measured in gemini contact. This result provides experimental evidence that the presence of these highly lubricious water films is strongly dependent on the polymer‐network structure at the surface. Spectroscopic and mechanical analysis of a polyacrylamide hydrogel surface reveals an extended gradient in polymer‐network density. The formation and nature of the gradient depends on mold hydrophobicity during polymerization. Low polymer volume fraction at the hydrogel surface leads to formation of a substantial water film at the interface, rendering the hydrogel highly lubricious, with sliding‐speed independent friction.